2007
DOI: 10.1208/pt0801001
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as an ocular delivery system for acetazolamide: In vitro and in vivo studies

Abstract: The purpose of this study was to formulate topically effective controlled release ophthalmic acetazolamide liposomal formulations. Reverse-phase evaporation and lipid film hydration methods were used for the preparation of reverse-phase evaporation (REVs) and multilamellar (MLVs) acetazolamide liposomes consisting of egg phosphatidylcholine (PC) and cholesterol (CH) in the molar ratios of (7:2), (7:4), (7:6), and (7:7) with or without stearylamine (SA) or dicetyl phosphate (DP) as positive and negative charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(170 citation statements)
references
References 35 publications
13
152
1
4
Order By: Relevance
“…This confirms the formation of the double layer structure of the vesicle, as reported previously. [32] No peak of BCT was observed in the drug-loaded formulation, indicating the amorphous nature of the drug. No major difference was observed in the thermograms of drug-free and drug-loaded proniosomes.…”
Section: Dsc Analysismentioning
confidence: 97%
“…This confirms the formation of the double layer structure of the vesicle, as reported previously. [32] No peak of BCT was observed in the drug-loaded formulation, indicating the amorphous nature of the drug. No major difference was observed in the thermograms of drug-free and drug-loaded proniosomes.…”
Section: Dsc Analysismentioning
confidence: 97%
“…Rollback was prevented using clamp. The cap was removed and gel extruded until the pressure was degenerated (Panigrahi et al 2006;Srisombat et al 2005;Dave et al 2010;Hathout et al 2007). …”
Section: Extrudabilitymentioning
confidence: 99%
“…7 Liposomal encapsulation protects drug molecules from enzymatic hydrolysis in the physiological environment while in circulation, and thus increases stability. Previous studies on topical application of liposomes demonstrated poor penetration into the eye, [8][9][10][11] however, while studies on subconjunctival injections on other IOP-lowering drugs showed limited sustainability. 9,11,12 Furthermore, it is not clearly understood whether drug-loaded liposomes in the subconjunctiva behave like a depot system or actually undergo circulation and endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on topical application of liposomes demonstrated poor penetration into the eye, [8][9][10][11] however, while studies on subconjunctival injections on other IOP-lowering drugs showed limited sustainability. 9,11,12 Furthermore, it is not clearly understood whether drug-loaded liposomes in the subconjunctiva behave like a depot system or actually undergo circulation and endocytosis. 12 The design of carriers for sustained delivery in the eye necessitates the use of a formulation that has the required optical clarity with sufficient drug loading efficiency for administration.…”
Section: Introductionmentioning
confidence: 99%